Popular romance and the woman reader - Nuttall, Sarah (Department of English Language and Literature, 2016)
'Popular Romance and the Woman Reader' is divided into three parts. The first is an analysis of theories of reading, of the woman reader and of how we read popular texts. The first section discusses women readers and popular romance in a Western context, with special reference to an American study by Janice Radway, Reading the Romance, and the second looks at how similar issues might apply amongst African women readers. Part II is a textual analysis of several romance texts. The final part is an account of four interviews in which black South African women talk about their romance reading. Although the focus of the study is on popular romance, I also intend it to re-examine the categories of 'woman reader' and 'black woman reader in South Africa'. As new freedoms are opened to the reader in South Africa, it is offered as a contribution to an understanding of how reading, and the construction of subjectivity itself, can be transformed in the future.